НОВАЯ ДЛЯ МОСКОВСКОЙ ОБЛАСТИ НАХОДКА ЖУКА-ПЛАВУНЦА (COLEOPTERA, DYTISCIDAE) ИЗ РОДА CYBISTER CURTIS, 1827 (Юг России: экология, развитие)
For the first time for the Moscow region a predaceous diving beetle Cybister lateralimarginalis (DeGeer, 1774), which is very rare here, is indicated. Its place of discovery and a short information about its area and biology are given.